A methanol VOC sensor using divalent metal ion-modified 2D DNA lattices1. Issue 83 (9th September 2015) - Kim, Hyeong-U; Dugasani, Sreekantha Reddy; Kulkarni, Atul; Gnapareddy, Bramaramba; Kim, Jang Ah; Park, Sung Ha; Kim, Taesung
<x xml:space="preserve">Abstract</x> Metal ion modified DNA synthesized by a substrate-assisted growth method were utilized for a VOC gas sensor. Co-DNA lattices with defined periodicity efficiently yield an enhancement in reflected intensities within TLV of methanol vapor selectively.